2020
DOI: 10.1292/jvms.20-0117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-concentrate corn grain diet-induced elevated ruminal lipopolysaccharide levels on dairy cow liver function

Abstract: A high-concentrate diet destroys gram-negative bacteria in the cattle rumen, leading to elevated ruminal lipopolysaccharide (LPS) levels. LPS causes liver inflammation through the hepatic portal vein but little is known about the effects of rumen-derived LPS on liver function and the reproductive organs. In this study, we determined the effect of increasing rumen fluid LPS levels on liver function and genital LPS levels. Cows were assigned to control (CON; n = 5) and highconcentrate diet (HC; n = 7) groups. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…HC diet‐derived LPS elicits acute phase response (APR) by regulating the synthesis and secretion of acute phase proteins (APPs) in liver thus any fluctuation in their concentrations in the peripheral blood reflects the functional disturbance and inflammation of liver (Guo et al, 2017 ; He et al, 2019 ; Minuti et al, 2015 ). Many studies have reported that HC diets increased levels of positive APPs and decreased negative APPs in peripheral blood of ruminants (Chandra et al, 2018 ; Ohtaki et al, 2020 ; Zhang et al, 2016 ) accompanied with alteration at transcriptional level in liver (Chishti et al, 2020 ; Li et al, 2019 ). Moreover, the modulation of hepatic APPs genes expressions in LPS‐challenged goats, sheep, and cattle (Cao et al, 2006 ; Jiang et al, 2008 ; Wang et al, 2017 ) indicate that HC diet induce hepatic inflammatory response through LPS translocated from GIT via portal vein (Chang, Zhang, Xu, Jin, Guo, et al, 2015 ; Chang, Zhang, Xu, Jin, Seyfert, et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HC diet‐derived LPS elicits acute phase response (APR) by regulating the synthesis and secretion of acute phase proteins (APPs) in liver thus any fluctuation in their concentrations in the peripheral blood reflects the functional disturbance and inflammation of liver (Guo et al, 2017 ; He et al, 2019 ; Minuti et al, 2015 ). Many studies have reported that HC diets increased levels of positive APPs and decreased negative APPs in peripheral blood of ruminants (Chandra et al, 2018 ; Ohtaki et al, 2020 ; Zhang et al, 2016 ) accompanied with alteration at transcriptional level in liver (Chishti et al, 2020 ; Li et al, 2019 ). Moreover, the modulation of hepatic APPs genes expressions in LPS‐challenged goats, sheep, and cattle (Cao et al, 2006 ; Jiang et al, 2008 ; Wang et al, 2017 ) indicate that HC diet induce hepatic inflammatory response through LPS translocated from GIT via portal vein (Chang, Zhang, Xu, Jin, Guo, et al, 2015 ; Chang, Zhang, Xu, Jin, Seyfert, et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in APPs levels in HC fed ruminants is found associated with changes in pro‐ and anti‐inflammatory cytokines levels in blood (Chang, Zhang, Xu, Jin, Seyfert, et al, 2015 ; Guo et al, 2017 ; Ohtaki et al, 2020 ). Concomitantly, we observed hepatic mRNA upregulation of TNF‐α, IL‐1β, IL‐10, and downregulation of IL‐13 in HC than in LC goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-energy diets have been shown to lower rumen pH and alter the composition of the intestinal microbiota. In addition, high energy diets have also been linked to increases in the amount of circulating LPS and LPS induced reductions in αβ T lymphocytes ( Klaudia & Alina, 2015 ; Ohtaki et al., 2020 ). Many researchers believe that high-energy feed should be considered as a background factor when evaluating immune function in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing concentrations of starch or dietary NFC can raise milk production in dairy cows and is favorable for use of energy and nitrogen in beef cattle output. However, excessive proportions of NFC/NDF may induce the risk of subclinical rumen acidosis, while a lower ratio of NFC/NDF may limit ruminant production performance [4,5]. Changing dietary roughage and concentrate contents is a common method to change dietary structure and nutrient level.…”
Section: Introductionmentioning
confidence: 99%